The Indian agents of Fort Chipewyan: bureaucrats in isolation - Mackenzie, Patrick Niven (University of Calgary, 1993)
Bibliography: p. 121-135. Until 1969, Indian agents in Canada formed the strongest link between the Indian Affairs Department, or Branch, and the status Indians of the country. They have received little specific scholarly attention , however. This thesis is a case study of the role played by the Indian agents in the northern Alberta community of Fort Chipewyan. The first three agents, resident in the settlement from 1932 to 1943 collectively, were physicians first, and Indian agents second. Jack Stewart, a Cree-speaking former fur trader, took over the agency in 1944, and soon assumed a strong leadership role in the community . Whatever their administrative styles, all of the agents shared local autonomy from the political side of Indian Affairs, a desire to see the Amerindians stay independent on their traplines, and, unfortunately, powerlessness in the face of the economic and social forces that would rob the Indians of their way of life.